Serodetection of Brucellosis using Rose Bengal Test (RBT) and Complement Fixation Test (CFT) Method in Dairy Cattle in Banyuwangi - Estiary Wilujeng (Journal of Basic Medical Veterinary, 2023)
The aim of this research to detect antibodies of the Bacteria Brucella in dairy cattle in Banyuwangi District using serological test. Serological tests that used in this research was Rose Bengal Test (RBT) to screening and than confirmed by Complement Fixation Test (CFT). Sample was determined by Slovin formula with a sample size of 84 samples from 516 dairy cattle of the Banyuwangi District and were taken by random. The samples in this reasearch were collected from serum of Dairy catlle. The method that used in this research was descriptive and analysis method with quantitative approach. Supporting information obtained from interviews. The results of this research was found that 2 sample positive Brucellosis that was tested by RBT and CFT. RBT is a screening test that can give a false positif, and then to confirmed that use CFT that can show difference titer result of vaccinated and natural infection. The incidence rate of the Brucellosis in the Banyuwangi District was 2%.